A Bradford multiplexing method for protein estimation in fermented foods: Soy sauces (Bangladesh Journal of Pharmacology, 2015)
Proteins for foods, in addition to providing nutrition, should also possess specific functional properties that facilitate processing and serve as the basis of product performance. Soy protein is a major component of the diet of food and is increasingly important in the human diet. Hence, here in the present article, we are focusing a rapid and easy method for quantitative determination of total protein content with multiplex samples in any food products such as soy sauce or other traditional fermented foods. We described a bioassay procedure (Bradford method) for the evaluation of total protein content in foods. This method involves measurement of the protein efficiency ratio under standardized conditions. The experiment will provide researchers a scientific way to determine pretentious quality of variety of foods and/or health supplements. Video Clips of Methodology:Requirement and sample preparation method: 3 min 26 sec   Full Screen   AlternateAssay procedure: 6 min   4 sec   Full Screen   AlternateMeasurement of absorbance using an ELISA microtiter plate reader: 5 min 1 sec   Full Screen   Alternate